Pengaruh Air Rebusan Daun Sirih Untuk Mengatasi Keputihan Pada Remaja Putri Di Desa K Kabupaten Purwakarta Tahun 2024 - Suciati, Tia; Sari , Santika (CV. Green Publisher Indonesia, 2025)
Vaginal discharge is one of the problems that occur in adolescents, because in Indonesia with a tropical climate it is one of the triggers of vaginal discharge. The humid climate makes the fungus grow quickly coupled with dense activities that make teenagers often experience vaginal discharge. Therefore, vaginal discharge is one of the problems that must be paid attention to by midwives so that women, especially teenagers, can maintain personal hygiene and feminine organs to prevent vaginal discharge and how to overcome it by using non-pharmacological therapy, one of which is betel leaf boiling water Objective: To find out the effect of betel leaf boiled water to treat vaginal discharge in adolescent girls Methods: This research is a type of experimental research with a pre-test, post-test, one group research design. The sample in this study is adolescent girls, with a sample size of 33 respondents. Sampling using accidental sampling technique, the instrument used was a questionnaire Results: The results of this study are that before using betel leaf decoction water the average whitiy score on the questionnaire is 10 - 16, while after using betel leaf decoction water the average whitish score is 7 - 10. Statistical tests using parametric tests, namely Paired Sample T-Test, obtained a significance value of p-value = 0.000 (p-value < 0.05), meaning that there is a significant difference in the vaginal discharge of adolescent girls and afterwards using betel leaf boiled water. Conclusion: There is an Effect of Leaf Boiled Water to Treat Vaginal Discharge in Adolescent Girls.